2020
DOI: 10.1186/s12889-020-09320-1
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and geographic variations in antenatal care coverage in Angola: further analysis of the 2015 demographic and health survey

Abstract: Background: In African countries, including Angola, antenatal care (ANC) coverage is suboptimal and maternal mortality is still high due to pregnancy and childbirth-related complications. There is evidence of disparities in the uptake of ANC services, however, little is known about both the socioeconomic and geographic-based disparity in the use of ANC services in Angola. The aim of this study was to assess the extent of socioeconomic , urban-rural and subnational inequality in ANC coverage in Angola. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
(42 reference statements)
9
32
0
Order By: Relevance
“…More specifically, we found that the likelihood of taking deworming medication was higher among pregnant married women who had attended secondary school compared to pregnant married women who had no formal education. BioMed Research International Several studies confirm that there is a significant association between maternal educational status and maternal health service utilization such as ANC [33,34] and uptake of deworming medication [28]. The possible reason for better uptake of maternal health service among educated women might be due to higher health knowledge among educated women as compared to noneducated [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, we found that the likelihood of taking deworming medication was higher among pregnant married women who had attended secondary school compared to pregnant married women who had no formal education. BioMed Research International Several studies confirm that there is a significant association between maternal educational status and maternal health service utilization such as ANC [33,34] and uptake of deworming medication [28]. The possible reason for better uptake of maternal health service among educated women might be due to higher health knowledge among educated women as compared to noneducated [35].…”
Section: Discussionmentioning
confidence: 99%
“…Having a better socioeconomic situation as a woman facilitates not only access or affordability of transport costs but also helpful in buying the medication whenever the health facilities have supply problem or not available in dispensary or drug store [36]. Evidence shows that the early beginning of ANC service [55] and higher uptake of ANC service are seen among pregnant married women in better socioeconomic status as compared to women in lower economic status [33,34,55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can pay for the consultation, medication, and other expenses associated with ANC services [27]. On the other hand, families with good socioeconomic status usually have their means of transportation, making it easier for pregnant women to come to the ANC service at any time [28].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning contextual factors; distance from a health facility, service waiting time, and client welcomed appreciation were associated with ANC services utilization. Besides, women's knowledge regarding ANC, the presence of electricity in households, and housing conditions were associated with ANC services utilization (8,9,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)10,(28)(29)(30)(31)(32)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%